Electroless Deposited Gold Nanoparticles on Glass Plates as Sensors for Measuring the Dielectric Constant of Solutions. (26th March 2013) - Kobayashi, Y.; Ishii, Y.
Abstract : This work describes a method for the deposition of Au nanoparticles on glass plates (Au-glass). An electroless metal plating technique was extended to the Au nanoparticle deposition. The technique consisted of three steps that took place on the glass plate: (1) adsorption of Sn 2+ ions, (2) deposition of metallic Ag nuclei generated by reducing Ag + ions with Sn 2+ ions on the Sn-adsorbed sites, and (3) deposition of Au nanoparticles by reducing Au + ions on the Ag surface. TEM observation revealed that metallic Au nanoparticles with a size of 34.6 ± 11.5 nm were formed on the glass surface. A surface plasmon resonance absorption peak was observed, and its peak wavelength redshifted by immersing the Au-glass into a solution with a large dielectric constant. The redshift corresponded qualitatively to the calculation by the Mie theory accompanying the Drude expression, which was based on the change of the dielectric constant of the solution. The obtained results indicated that the Au-glass functioned as a sensor for measuring the dielectric constant of the solution.